Association of attention and memory biases for negative stimuli with post-traumatic stress disorder symptoms. (January 2022) - Imbriano, Gabriella; Waszczuk, Monika; Rajaram, Suparna; Ruggero, Camilo; Miao, Jiaju; Clouston, Sean; Luft, Benjamin; Kotov, Roman; Mohanty, Aprajita
Abstract: Cognitive models have highlighted the role of attentional and memory biases towards negatively-valenced emotional stimuli in the maintenance of post-traumatic stress disorder (PTSD). However, previous research has focused mainly on attentional biases towards distracting (task-irrelevant) negative stimuli. Furthermore, attentional and memory biases have been examined in isolation and the links between them remain underexplored. We manipulated attention during encoding of trauma-unrelated negative and neutral words and examined the differential relationship of their encoding and recall with PTSD symptoms. Responders to the World Trade Center disaster (N = 392) performed tasks in which they read negative and neutral words and reported the color of another set of such words. Subsequently, participants used word stems to aid retrieval of words shown earlier. PTSD symptoms were associated with slower response times for negative versus neutral words in the word-reading task ( r  = 0.170) but not color-naming task. Furthermore, greater PTSD symptom severity was associated with more accurate recall of negative versus neutral words, irrespective of whether words were encoded during word-reading or color-naming tasks ( F  = 4.11, p  = 0.044, ηp 2 = 0.018). Our results show that PTSD symptoms in a trauma-exposed population are related to encoding of trauma-unrelated negative versus neutral stimuli only when attention was voluntarily directed towards the emotional aspects of the stimuli and to subsequent recall of negative stimuli, irrespective of attention during encoding. Highlights: Attentional biases to negative stimuli and their relationship with memory biases in PTSD are understudied. Higher PTSD symptoms predicted slower encoding of negative versus neutral words when emotion was voluntarily attended to. Higher PTSD symptoms were associated with more accurate recall of negative versus neutral words. Attention voluntarily directed towards negative stimuli and their greater recall may be important PTSD treatment targets.